Leading with Commitment: The Mediating Role of Work Discipline in Enhancing Civil Servant Performance - Wulandari, Andrie Resita; Kadarusman (Indonesian Journal of Business Analytics, 2025)
This study examines the impact of leadership and organizational commitment on civil servant performance, with work discipline as a mediating variable, at the Livestock and Animal Health Service of Malang Regency. Using a quantitative survey approach, data were collected from 104 respondents selected via the Slovin formula. Analysis was conducted using PLS-SEM with SmartPLS. Findings reveal that leadership and commitment significantly influence work discipline, which in turn positively affects performance. Moreover, work discipline mediates the relationship between leadership, commitment, and performance. The study concludes that enhancing civil servant performance requires strengthening leadership, fostering organizational commitment, and enforcing discipline as a strategic lever.